Tuberculosis Mimicking-Musculoskeletal Tumor of The Hand: An Uncommon Case of Extrapulmonary Tuberculosis - Andy Lesmana; Hapsari Retno Dewanti; Lenty BR Perangin Angin; Muhamad Irvan Muzakky; Stefi Geovani Valentin Hayon; Mentari Maratus Sholihah; Muhammad Ifham Hanif (Universitas Airlangga, 2023)
Background: Musculoskeletal extrapulmonary tuberculosis is accounting for only 10-15% of all cases. Current attention has been focused on hand tuberculosis due to its increasing prevalence. This study describes an unusual case of extrapulmonary tuberculosis that manifested as a soft tissue tumor of the hand.Case Report: A 17-year-old male presented with a painful swollen part of the 3rd finger of the left hand. The mass was irregular and suppurative, with discoloration and foul smell. Laboratory results showed anemia and increased erythrocyte sedimentation rate. The computed tomography scan showed an isodense soft tissue (size 2.19 cm x 1.59 cm x 4.21cm) across the distal to the proximal part of 3rd phalanx bone to the metacarpal region with a decrease of phalanx bone density with no sign of bone destruction or any periosteal reaction. The histopathology study revealed a chronic granulomatous structure surrounded by epitheloid cells, datia Langhans cells, and caseating necrosis. The acid-fast staining confirmed the presence of bacilliform bacteria.Discussion: Extrapulmonary tuberculosis typically results from secondary hematogenous dissemination and reactivation of the main foci. There are no specific tests to diagnose musculoskeletal tuberculosis preoperatively, leading to delayed diagnosis. Histopathological examination and culture are needed to confirm the diagnosis.Conclusions: Slow progression and multiple differential diagnoses frequently result in a delayed diagnosis, which leads to complications. Initial radical excision and anti-tuberculosis multidrug therapy provide excellent functional outcomes and recurrence prevention.